DIGITAL MARKETING OF SERPONG URBANTOWN APARTMENTS TO INCREASE BRAND AWARENESS AND CUSTOMER SATISFACTION - Kevin Lye; Rudi Santoso (Journal of Applied Management and Business, 2021)
This research focuses on the efforts of Apartment Urbantown Serpong to increase Brand Awareness. The strategy offered in this research is marketing communication using digital marketing. The use of social media in marketing communications in this study aims to provide a different perspective or point of view from the activities of the digital marketing process. This study also examines digital marketing strategies to increase Brand Awareness Apartment Urbantown Serpong. This study uses a qualitative descriptive method with a literature review approach. The results show that digital marketing strategies are proven to be able to increase brand awareness. The indicator used in this study is the impact or response from research sources to identify the Serpong Urbantown Apartment brand.